HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR IPS - Khalida Rozana Ulfah; Anang Santoso; Sugeng Utaya (Graduate School of Universitas Negeri Malang, 2016)
The purpose of this study describes the relationship between motivation and learning outcomes, and how the relationship between motivation with student learning outcomes. This type of research is descriptive correlational models person. Collecting data using questionnaires and documents with the object of fifth grade students of SDN Melayu 2 Banjarmasin. Data were analyzed using Pearson correlation analysis. The results of data analysis known that most students have high motivation and learning outcomes, correlation values obtained Pearson r hitung of 0.283 with significance value = 0.043. rtabel with degrees of freedom (df = 54) for α = 0.05 value obtained 0.259. The next step to do a comparison, where the value is greater than rtabel rhitung (0.283> 0.259), and in addition the significant value gained more than α = 0.05 (0.035> 0.05) so that it can be concluded there is a relationship of motivation with learning outcomes.Tujuan penelitian ini menjelaskan hubungan motivasi dan hasil belajar, serta bagaimana hubungan motivasi dengan hasil belajar siswa. Jenis penelitian adalah deskriptif korelasional model person. Pengumpulan data menggunakan angket dan dokumen dengan objek siswa kelas V SDN Melayu 2 Banjarmasin. Teknik analisis data menggunakan analisis korelasi Pearson. Hasil analisis data diketahui bahwa sebagian besar siswa memiliki motivasi dan hasil belajar tinggi, uji korelasi Pearsondidapatkan nilai rhitung sebesar 0,283 dengan nilai Signifikansi = 0,043. rtabel dengan derajat bebas (df=54) untuk α = 0,05 didapatkan nilai 0,259. Langkah selanjutnya dilakukan perbandingan, di mana nilai rhitung lebihbesar daripada rtabel (0,283 > 0,259). Selain itu, nilai signifikansi yang diperoleh lebih dari α = 0,05 (0,035 > 0,05) sehingga dapat disimpulkan terdapat hubungan motivasi dengan hasil belajar.